THE DEVELOPMENT OF PUBLIC EDUCATION AND THE SOCIAL SCIENCES IN TURKESTAN DURING THE FIRST YEARS OF SOVIET RULE - Qodirova R. M. (TARIXIY TADQIQOTLAR, 2026)
The article examines the development of school education and the system of public education in Turkestan during 1917–1925, as well as the process of teaching history and social studies in schools. It covers the establishment of Soviet schools following the Bolsheviks’ rise to power, the organization of national schools in native languages, issues with textbooks and teaching aids, the replacement of history by social studies, and changes in pedagogical methods. The study highlights the historical context of early Soviet educational policy in the Turkestan ASSR and the ideological and political education of the youth.